Disproportionality and Business Cycle from Tugan-Baranovskij to Spiethoff - Ferlito, Carmelo (Journal of Reviews on Global Economics, 2015)
In the second half of the 19th century, German-speaking countries developed a very intense economic debate about crises. Mikhail Ivanovich Tugan-Baranovskij’s analysis may be considered as the point of transition between different crisis theories and the development of organic thinking about the business cycle. It was an integral part of the German debate and had a decisive influence on Arthur Spiethoff’s elaboration - perhaps the most organic analysis of the cycle developed within the German historical school. Arthurs Spiethoff’s influence was recognized by important authors such as Friedrich A. von Hayek and Joseph A. Schumpeter. Both the Austrian economists admitted their debt toward the German scholar in elaborating their business cycle theories. The present paper aims to illustrate one of the important roots in Spiethoff’s approach, an approach that in turn became a crucial reference for other important economists.